Neutrophils: Accomplices in metastasis. (1st November 2020) - Zhu, Kunjie; Li, Panchun; Mo, Yongzhen; Wang, Jie; Jiang, Xianjie; Ge, Junshang; Huang, Weilun; Liu, Yan; Tang, Yanyan; Gong, Zhaojian; Liao, Qianjin; Li, Xiaoling; et al.
Abstract: Metastasis is a critical cause of treatment failure and death in patients with advanced malignancies. Tumor cells can leave the primary site and enter the bloodstream; these circulating tumor cells then colonize target organs by overcoming blood shear stress, evading immune surveillance, and silencing the offensive capabilities of immune cells, eventually forming metastatic foci. From leaving the primary focus to the completion of distant metastasis, malignant tumor cells are supported and/or antagonized by certain immune cells. In particular, it has been found that myeloid granulocytes play an important role in this process. This review therefore aims to comprehensively describe the significance of neutrophils in solid tumor metastasis in terms of their supporting role in initiating the invasion and migration of tumor cells and assisting the colonization of circulating tumor cells in distant target organs, with the hope of providing insight into and ideas for anti-tumor metastasis treatment of tumor patients. Highlights: Metastasis is the leading cause of death in cancer patients Neutrophils participate in the metastatic cascade of tumor cells, helping circulating tumor cells to build successful metastases in secondary organs Neutrophils are expected to become emerging targets for immunotherapy